Regressão binária usando ligações potência e reversa de potência - Chumbimune Anyosa, Susan Alicia (2017)
The aim of this dissertation is to study a family of asymmetric link functions for binary regression models under Bayesian approach. Specifically, we present the estimation of parameters of power and reversal power binary regression models considering Hamiltonian Monte Carlo method, on No-U-Turn Sampler extension, and Metropolis-Hastings within Gibbs sampling method. Furthermore, we study a wide variety of model comparison measures, including information criteria and measures of predictive evaluation. A simulation study was conducted in order to research accuracy and efficiency on estimated parameters. Through analysis of educational data we show that models using the proposed link functions perform better fit than models using standard links.